Mathematics for nonlinear phenomena -- analysis and computation : in honor of Yoshikazu Giga's 60th Birthday, Sapporo, Japan, August 2015 /: in honor of Yoshikazu Giga's 60th Birthday, Sapporo, Japan, August 2015. (2017) - Unknown
No abstract available